DIGITAL LEARNING REVOLUTION: A COMPARATIVE ANALYSIS OF NPTEL, NDL, SWAYAM, AND E-PG PATHSHALA IN INDIA'S EDUCATIONAL LANDSCAPE (LIS TODAY, 2023)
The digital era has brought about a revolutionary transformation in the field of  education, particularly in India, where various online platforms have emerged to supplement  traditional learning methods. This paper presents a comprehensive comparative analysis of  four prominent digital learning platforms in India: NPTEL (National Programme on  Technology Enhanced Learning), NDL (National Digital Library), SWAYAM (Study Webs of  Active-Learning for Young Aspiring Minds), and e-PG Pathshala. The study aims to evaluate  their impact, effectiveness, and contribution to India's educational landscape. This study compares four major digital learning platforms in India – NPTEL, NDL,  SWAYAM, and e-PG Pathshala – to assess their impact on education. Examining aspects like  content diversity, accessibility, and user satisfaction, we find NPTEL excels in tech education,  NDL is a comprehensive digital library, SWAYAM promotes interactive learning, and e-PG  Pathshala focuses on postgraduate education. Challenges like internet connectivity and  digital literacy are noted. Recommendations include increased collaboration and enhanced  user support. This analysis informs policymakers and educators navigating the evolving  landscape of digital education in India. This comparative study will provide valuable insights for educators, policymakers,  and e-learning platform developers in India. It will help them understand the strengths and  weaknesses of these platforms, allowing for informed decisions on how to enhance the  learning experiences of students across the country. Additionally, the study may contribute to  the broader discourse on the role of e-learning in shaping the future of education in India.
Keywords: Digital Learning Revolution; Online Education; Distance Learning; Learning Platforms; Skill Development; Virtual Classroom; Artificial Intelligence